The New Face of Terrorism: Global and National Challenges - Rosa, Jean (Indonesian Journal of Counter Terrorism and National Security, 2024)
In the contemporary landscape, terrorism has metamorphosed into a multifaceted and dynamic threat, manifesting in diverse forms on both global and national fronts. This paper investigates the intricacies of this evolving phenomenon, shedding light on its new face amidst shifting geopolitical paradigms and technological advancements. Through an exploration of the complex interplay between state and non-state actors, as well as the proliferation of diverse ideologies, it elucidates the challenges posed by modern terrorism at both global and national levels. The analysis encompasses the emergence of asymmetrical warfare tactics, the proliferation of transnational networks, and the diversification of ideological motivations driving terrorist activities. Moreover, it delves into the specific challenges faced by nations, including the rise of domestic radicalization, lone wolf attacks, and vulnerabilities in security infrastructure. By examining these issues, this paper aims to provide a comprehensive understanding of the contemporary terrorism landscape, highlighting the imperative for international cooperation, enhanced cybersecurity measures, and community engagement strategies in countering this pervasive threat. Through case studies and projections for future trends, it offers valuable insights for policymakers and practitioners tasked with addressing the complexities of terrorism in the 21st century.